Efeito Diabetes mellitus gestacional na modulação de genes relacionados ao metabolismo mitocondrial e a implicação na predisposiçao do recém-nascido à obesidade - Silveira, Maruhen Amir Datsch [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Obesity is a multifactorial disease involving complexes interactions between genetic and environmental agents. However, the increased incidence, early onset and severity of this disease, are still not well understood. Several findings have demonstrated that in utero stressors (diabetes, cigarettes, and/or alcohol consumption, etc) can promote genetic and epigenetic changes predisposing to late development of diseases and metabolic disorders, such as obesity. The present study was designed to evaluate the possible relationship between gestational Diabetes mellitus (GDM) and newborn predisposition to obesity his later life. Healthy and GDM pregnant women and their respective newborns were included. Additionally, obese and eutrophic adults were recruted as reference population. Considering the relationship between diabetes and obesity with mitochondrial dysfunction, gene and protein related to mitochondrial metabolism (SOD2 (superoxide dismutase 2), PPARα (peroxisome proliferator-activated receptor alpha) and PPARGC-1β(peroxisome proliferatoractivated receptor gamma coactivador beta) were evaluated in cells from cord and peripheral blood (reference population), and in placenta cells (gene expression profile in maternal and fetal sides). Our results showed an increased gene and protein expression (SOD2, PPARα and PPARGC-1β) in peripheral blood from obese compared to euthrophic subjects (p <0.05). However, the same result was not observed in the placental tissue (gene expression) and in umbilical cord blood cells (gene and protein expression) from GDM women and their respective newborn compared to the non diabetic group, i.e., GDM was not an effective agent to promote transcriptional changes in SOD2, PPARα PPARGC-1β in maternal and fetal sides of placenta, and transcriptional and translational changes in umbilical cord blood cells. In conclusion, SOD2, PPARα and PPARGC-1β gene and protein expression were confirmed as potential ...

A obesidade é uma doença de etiologia multifatorial, resultante de interações complexas entre fatores genéticos e ambientais. No entanto, o aumento acentuado de sua incidência, precocidade e severidade não foram ainda totalmente elucidados. Dentre os inúmeros fatores de risco, diversos achados sugerem, também, que estímulos estressores (p.ex. diabete, alterações nutricionais) na vida intrauterina podem promover alterações genéticas e epigenéticas, predispondo ao desenvolvimento tardio de doenças e disfunções metabólicas, como a obesidade. Assim, o presente estudo foi delineado com o objetivo de avaliar a possível relação entre o Diabetes melittus gestacional (DMG) e a predisposição do recém-nascido para o desenvolvimento de obesidade na vida adulta. Para tanto, foram incluídos no estudo gestantes saudáveis e gestantes diagnosticadas com DMG e seus respectivos recém-nascidos. Adicionalmente, adultos obesos e eutróficos foram incluídos como população de referência (controle). Considerando a relação entre o diabete e a obesidade com a disfunção mitocondrial, foi avaliado o perfil de expressão de gênica e proteica de SOD2 (superóxido desmutase 2), PPARα (receptor ativador da proliferação de peroxissomos alfa) e PPARGC-1β (receptor ativador da proliferação de peroxissomos gamma coativador 1 beta), relacionados ao metabolismo mitocondrial, em sangue do cordão umbilical e sangue periférico (população de referência), e o perfil de expressão gênica em células de placenta (faces materna e fetal). Primeiramente, nossos resultados demonstraram que indivíduos obesos apresentavam aumento da expressão gênica e proteica de SOD2, PPARα e PPARGC-1β no tecido sanguíneo quando comparados aos eutróficos (p < 0,05). No entanto, o mesmo não foi observado no tecido placentário (expressão gênica) e no sangue do cordão umbilical (expressão gênica e protéica) dos recém-nascidos das gestantes com DMG e...
Keywords: Diabetes mellitus; Diabetes na gravidez; Expressão gênica; Obesidade; Recém-nascidos - Metabolismo; Newborn infants - Metabolism